2006
DOI: 10.1095/biolreprod.105.046219
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of GM1 with Cholera Toxin B in Live Epididymal Versus Ejaculated Bull, Mouse, and Human Spermatozoa1

Abstract: The organization of membrane subdomains in mammalian sperm has recently generated controversy, with several reports describing widely differing localization patterns for the ganglioside GM1. Using the pentameric B subunit of cholera toxin (CTB), we found GM1 to be restricted to the plasma membrane overlying the acrosome in the heads of live murine sperm. Interestingly, CTB had minimal binding to live bovine and human sperm. To investigate whether this difference in GM1 localization was because of species diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 54 publications
2
31
0
2
Order By: Relevance
“…GM1 is a characteristic component and reliable biomarker of lipid rafts. Other studies showed that it dynamically moves with methyl--cyclodextrin (M--CD) treatment in the mouse sperm membrane (Buttke et al, 2006;Selvaraj et al, 2007). Here, we found that M-…”
Section: Introductionmentioning
confidence: 62%
“…GM1 is a characteristic component and reliable biomarker of lipid rafts. Other studies showed that it dynamically moves with methyl--cyclodextrin (M--CD) treatment in the mouse sperm membrane (Buttke et al, 2006;Selvaraj et al, 2007). Here, we found that M-…”
Section: Introductionmentioning
confidence: 62%
“…The endogenous ganglioside GM1 has been found in the plasma membrane overlying the acrosome of the sperm head in several mammalian species 44 or over the whole sperm surface in human spermatozoa. 45 GM1 is known to influence several signalling pathways in somatic cells and its importance in sperm functional maturation, such as capacitation, has been recently established.…”
Section: Gangliosides and Spermatozoamentioning
confidence: 99%
“…It has been localized in lipid raft microdomains, which serve as platforms for the assembly of key recognition molecules on the sperm surface during capacitation. [44][45][46][47] In animal sperm, increasing evidence suggests that capacitation is regulated by the redistribution of GM1 on the plasma membrane. 48 For example, when murine sperm migrate to the uterine cavity, GM1 shifts from the postacrosomal region and disappears from the sperm head in the oviduct, at which time, spermatozoa can undergo the acrosome reaction.…”
Section: Gangliosides and Spermatozoamentioning
confidence: 99%
“…Conversely, GM1 was reported as nonexistent or patchy and inconsistent throughout the whole sperm cell of human and boar . One likely difference among these studies could be the fixation procedure [60], which might affect viability. In fact, it has been reported that GM1 moves rapidly from its position overlying the acrosome to the post-acrosomal area after cell death in unfixed or lightly fixed samples [59].…”
Section: Discussionmentioning
confidence: 99%